Micromechanical analysis of bioresorbable PLLA/Mg composites coated with MgO: Effects of particle weight fraction, particle/matrix interface bonding strength and interphase. (1st April 2019) - Mozafari, Hozhabr; Dong, Pengfei; Ren, Kewei; Han, Xinwei; Gu, Linxia
Abstract: Magnesium (Mg) particle has been recently introduced in a poly-l -lactic acid (PLLA) matrix to enhance to its mechanical properties. The coating of Mg particle could also regulate its degradation rate. In this work, the mechanical behavior of PLLA/Mg composite was characterized using a three-dimensional representative volume element (RVE) model. The influences of Mg weight fraction, imperfect bonding between particle and polymer matrix, and the interphase layer on the mechanical behaviors of the composites were quantified. Results clearly demonstrated that the effective Young's modulus and yield strength of the composite were enhanced by the Mg particles, as well as its MgO coating. In addition, the imperfect interfacial bonding between the Mg particle and PLLA weakened the mechanical advantage of the composite, which was in good agreement with the documented experimental observations. This work might shed some light on the optimal design and manufacturing of the bioresorbable composites.